Chikungunya virus–associated encephalitis: A cohort study on La Réunion Island, 2005–2009. (5th January 2016) - Gérardin, Patrick; Couderc, Thérèse; Bintner, Marc; Tournebize, Patrice; Renouil, Michel; Lémant, Jérome; Boisson, Véronique; Borgherini, Gianandrea; Staikowsky, Frédérik; Schramm, Frédéric; Lecuit, Marc; Michault, Alain
Abstract : Objective: To estimate the cumulative incidence rate (CIR) of Chikungunya virus (CHIKV)–associated CNS disease during the La Réunion outbreak, and assess the disease burden and patient outcome after 3 years. Methods: CHIKV-associated CNS disease was characterized retrospectively in a cohort of patients with positive CHIKV reverse transcriptase PCR or anti-CHIKV immunoglobulin M antibodies in the CSF and fulfilling International Encephalitis Consortium criteria for encephalitis or encephalopathy. Neurologic sequelae were assessed after 3 years. Results: Between September 2005 and June 2006, 57 patients were diagnosed with CHIKV-associated CNS disease, including 24 with CHIKV-associated encephalitis, the latter corresponding to a CIR of 8.6 per 100, 000 persons. Patients with encephalitis were observed at both extremes of age categories. CIR per 100, 000 persons were 187 and 37 in patients below 1 year and over 65 years, respectively, both far superior to those of cumulated causes of encephalitis in the United States in these age categories. The case-fatality rate of CHIKV-associated encephalitis was 16.6% and the proportion of children discharged with persistent disabilities estimated between 30% and 45%. Beyond the neonatal period, the clinical presentation and outcomes were less severe in infants than in adults. Conclusions: In the context of a large outbreak, CHIKV is a significant cause of CNS disease. As with other etiologies, CHIKV-associated encephalitis case distribution by age follows a U-shaped parabolic curve.